ANALYSIS OF FREE SEX BEHAVIOR IN SENIOR HIGH SCHOOL - Ayu Widiyanti; Dianita Ekawati; Helen Evelina (Majalah Kedokteran Sriwijaya, 2020)
Sexual behavior is all behavior driven by sexual desire. The purpose of this study was to analyze free sexual behavior in students at senior high scholl. The population in this study were all students at SMA Negeri 1 Muara Telang and the sample taken in this study was 83 respondents using probability sampling techniques, with a proportionate stratified random sampling. Research shows that there is a relationship between free sex behavior in adolescents with the role of school (P = 0.002, OR = 5,278, 95% CI = 1.8-14.7), the role of peers (p = 0.002, OR = 5.769.95% CI = 1.9- 17), knowledge (p = 0.004, OR = 5.280, 95% CI = 1.7-16), exposure to pornography (p = 0.004, OR = 5,280.95% CI = 1.7-16 ), attitude (P = 0.001, OR = 6.109.95% CI = 2.1-17), use of technology (p = 0.000, OR = 49.263, 95% CI = 6.19-392), Family support (p = 0.002, OR = 5,278, 95% CI = 1.8-14.7) and there was no relationship between free sex behavior and lifestyle (P = 0.082, OR = 2.612.95% CI = 0.9-6.8). With the most dominant variable in free sex behavior, the use of technology has a p-value of 0.003 and OR = 57,631, meaning that respondents who have free sex behavior have a 57,631 times greater risk of free sex behavior among SMA Negeri 1 Muara Telang students, Banyuasin Regency in 2020.The most dominant factor or the factor that most influences free sex behavior is the use of technology because the rapid development of technology makes it easier to find information on things that are negative or positive. It is recommended that schools monitor the use of technology in SMA Negeri 1 Muara Telang by appealing to parents to assist in the use of technology media.